(untitled) (Revista Argentina de Musicología, 2018)
Different aspects of Humahuaca Trio’s musical works are described and analyzed. In its repertory there is a fusion of several expressions of the so called folk music with rock and ska. The working hipothesis is that this group makes use of parody for producing a convergence among various musical genres. Parody is brounght into play not only in the fusion of different languages and themes, but also in the instrumentation and in the lyrics of the songs. Likewise it is claimed that parody in literary and musical fields is essentially a type of critique from a humorous perspective. So Humahuaca Trio identifies a set of stereotypes belonging to culture of Jujuy. The musical group criticizes life conditions produced by globalization in the Quebrada and Puna regions.